engaruh Motivasi Kerja dan Budaya Organisasi Terhadap Kinerja Karyawan Bank Syariah - Nursatrio Adi Prakosa (Universitas Multimedia Nusantara, 2011)
This research is a causal The purpose of this research was to determine the effect of motivation and organizational culture on employees’ performance of Islamic banks. The object in this study are the employees of Syariah Mandiri bank located in Jakarta area and Muamalat bank located in Bekasi area, which amounted to 101 respondents. Tests used in this research are validity test, reliability test, classic assumptions test, and hypotheses test using multiple linear regression analysis. The result of this research showed that motivation and organization culture have significant impact towards employees’ performance on Islamic banks both partially and simultaneously. Keyword: motivation, organizational culture, performance